The Influence of Recruitment and e- Government on Organizational Performance in Higher Education Institutions: A Strategic Management Perspective with Religiosity Mediation - Kumoro, Dwi Ferdiyatmoko Cahya; Maswanto; Sukirman; Nuryadi, Syafaat (IJOSMAS, 2025)
This study aims to investigate the effect of recruitment and e-government implementation on organizational performance in higher education institutions, with religiosity as a mediating variable. Amidst the dynamics of higher education institutions in Indonesia that face challenges to improve performance, this study uses a quantitative approach with data analysis through SmartPLS 4.0, based on an online survey of 1045 respondents selected by stratified random sampling. The findings show that transparent and competency-based recruitment, as well as the implementation of e-government, have a direct significant influence on improving organizational performance. In addition, religiosity is proven to function as a mediator that strengthens the relationship between recruitment and e-government on organizational performance. The results of this study indicate that the development of effective recruitment practices and the implementation of e-government can not only contribute directly to performance, but also indirectly through increased religiosity that extols the values of integrity, responsibility, and work ethics. The findings make theoretical contributions to the human resource management literature and excellent practices in the context of higher education, as well as offer practical recommendations for managers of educational institutions to integrate religious values in their management strategies.